A Proposed Model for Measuring the Relationship between Entrepreneurial Marketing and Marketing Performance with the Presence of Marketing Citizenship as an Intermediate Variable «An Applied Study on the Marketing Departments of Mobile Telecommunication S - Abdullah, Motaz (The Arab Journal of Administration, 2022)
The study aims at understanding the reality of entrepreneurial marketing in the marketing departments of mobile telecommunications service providers in Saudi Arabia. It also aims at understanding the effect of entrepreneurial marketing on the marketing performance with the existence of marketing citizenship as an intermediate variable. The researcher used the descriptive analytical method. A questionnaire was also written and included the axes of entrepreneurial marketing, marketing performance, and marketing citizenship. The study sample covered 139 employees of the total marketing departments of mobile telecommunications providers’ employees in Riyadh region (the basic centers of mobile telecommunications providers in Saudi Arabia that are located in Riyadh). The outcomes of the study primarily point out that the five basic mobile telecommunications companies are overall interested in entrepreneurial marketing. On the top of these companies’ interests comes the creative and innovative part of entrepreneurial marketing and at the bottom comes the part of risk management. The study also indicates that there is a connection of a statistical significance between entrepreneurial marketing in its dimensions: creativity and innovation, value creation and pro-activity, concentrating on the client, and leading and directing opportunities and marketing citizenship. Moreover, the study recommended on the importance of conducting more studies to find out the factors that lead to raising the level of entrepreneurial marketing including all of its dimensions and the marketing performance and its dimensions as this has a considerable impact on the economy of the KSA. In addition to that, the study recommends that it is necessary to keep this high level and improve it whenever possible. Also, the elements and components of marketing citizenship should be given vital importance for the role they play in improving the marketing performance.